An exploration study on factors influencing Iranian food industry - Arash Hosseinzadeh; Seyed Mohsen Seyedaliakbar; Naser Azad; Ashkan Arabi (Management Science Letters, 2013)
The proposed study of this paper present an empirical investigation to detect important factors impacting on food market using factor analysis. The proposed study designed a questionnaire, distributed among 207 customers who were regular customers of two food chains in city of Tehran, Iran named Shahrvand and Hyperstar. The results of our survey indicate that six major factors including brand loyalty, physical characteristics, pricing effects, performance characteristics, brand relationship and brand position influence food industry, significantly. In terms of the first factor, brand loyalty, “Trust”, “Packaging design characteristics”, “Competitive pricing strategy”, “Stability in quality”, “External relationships” and “Meeting expectations” are important factors in different categories.